Physiological and transcriptomic analyses of response of walnuts (Juglans regia) to Pantoea agglomerans infection - An, Xiu-Hong; Wang, Ning; Wang, Hongxia; Li, Yan; Si, Xiao-Yu; Zhao, Shugang; Tian, Yi (Frontiers in Plant Science, 2023)
Introduction Walnut blight is a serious bacterial disease that affects the yield and quality of walnuts. Pantoea agglomerans is one of the main causative agents of walnut blight. However, there have been few studies on the response of walnuts to P. agglomerans infection. Methods In this study, the soluble sugar, photosynthesis, antioxidant enzyme activities, and secondary metabolites were measured, and the transcriptomic analysis was performed to determine the response of walnut tissue cultures to P. agglomerans infection. Results After pathogen inoculation, the soluble sugar content decreased, and photosynthesis was inhibited. Antioxidant enzyme (superoxide dismutase and peroxidase) activities and secondary metabolites (phenol and flavonoid) contents increased, especially in the early stages of inoculation. Transcriptomic analysis revealed that the phenylpropanoid biosynthesis pathway is induced after infection, and pathogen infection promotes ABA and ethylene signal transduction and inhibits auxin signaling. In addition, SA and JA-related gene expression was altered after inoculation with P. agglomerans, and the FLS- and calcium-mediated disease resistance signaling pathways were activated. Furthermore, our results suggested an involvement of the R-protein RPM-mediated disease resistance pathway in the response of walnuts to bacterial infections. Discussion Our findings indicated that phenylpropanoid biosynthesis, hormone signal transduction, and plant-pathogen interaction have key roles in pathogenic inoculation, which provide insights into the molecular mechanisms in the response of walnuts to P. agglomerans infection.